Sustainable engineering and Internet of Things (IoT): Trends and perspectives (2020)
Internet of Things – IoT appeared in the forecast of engineering three decades ago. Since then, a vast range of applications has been developed in industrial, urban, and rural matters, where one of the most relevant issues has been sustainability. This paper presents a retrospective analysis of the most relevant trends in sustainability regarding IoT and its applications, considering evolution trends and tangible results from the last decade (2011-2020). When the concept of sustainability in engineering gained importance. The study provides useful insights into the future development of IoT in human life and industrial activities as well as research opportunities in terms of sustainability based on IoT approaches.